Effect of insulin on the intestinal absorption of glucose (Revista Española de Fisiología, 1951)
The intravenous administraron of Insulin (2 units per 100 g. weight) produces in normal rats an inmediato and temporary increase in the ability oí absorption oí glucose from the intestino. The possible influences oí hormones on enzymes oí the intestinal epithelium in relation to glucose absorption are discussed.